Determining the Soil Elements Distribution of a Google Earth Image Using a New Processing Method: A Case Study in Iraq - Abood, Khaleel Ibrahim; Zaeen, Ahmed Asaad; Mahmood, Faleh Hassan (Iraqi Journal of Science, 2025)
The study uses the photometric method, which depends on the intensity of color scale levels in the image pixels. The work is based on converting color into a wavelength in each pixel; in the beginning, the work has been verified by measuring the monochromatic wavelengths of rays, such as lasers. The Matlab program (image processing) calculated the number of lasers as 325 nm, 473 nm, 477 nm, 535 nm, 603, and 785 nm, where the results were very good and had a low error rate. The elements had distinctive colors, which indicated wavelengths in the visible range. The work was done for the sulfur element found in specific Iraqi locations, such as Al-Mashraq field in Mosul province. The image processing techniques by Matlab software, with the assistance of the Google Earth tool, zoomed the land from a scale of about 700 km to 5m, as shown in the research results. The result showed that the sulfur element locations on the map revealed that Iraq contains significant quantities of the element in western and southwestern regions, which essentially concentrate in referred locations compared to some fields in northern Iraq. This study and its results can help companies identify specific sulfur fields.